2-[(3,5-Di-tert-butyl-4-hydroxybenzyl)sulfanyl]-N'-isopropylideneaceto-hydrazide - Ariffin, Azhar; Ng, S.W.; Yehye, W.A. (International Union of Crystallography, 2009)
The title compound, C(20)H(32)N(2)O(2)S, the condensation product of a thioacetohydrazine and acetone, has a two-coordinate S atom and the angle at this atom is 100.7(1)degrees. The (CH(3))C=N-NH-C(O)- substituent engages in N-H center dot center dot center dot O hydrogen-bonding interactions with the substituent of an adjacent molecule across a center of inversion, generating a dimeric structure.